Women artists at the millennium - Armstrong, Carol M.; Zegher, M. Catherine de (MIT Press, 2006)
"More than thirty years after the birth of the modern women's movement and the beginnings of feminist art-making and art history, the time is ripe to examine the legacies of those revolutions. In Women Artists at the Millennium, artists, art historians, and critics examine the differences that feminist art practice and critical theory have made in late twentieth-century art and the discourses surrounding it. In 1971, when Linda Nochlin published her essay "Why Have There Been No Great Women Artists?" in a special issue of Art News, there were no women's studies, no feminist theory, no such thing as feminist art criticism; there was instead a focus on the mythic figure of the great (male) artist through history. Since then, the "woman artist" has not simply been assimilated into the canon of "greatness" but has expanded art-making into a multiplicity of practices with new parameters and perspectives. In Women Artists at the Millennium artists including Martha Rosler and Yvonne Rainer reflect upon their own varied practices and art historians discuss the innovative work of such figures as Louise Bourgeois, Lygia Clark, Mona Hatoum, and Carrie Mae Weems. And Linda Nochlin considers changes since her landmark essay and looks to the future, writing, "We will need all our wit and courage to make sure that women's voices are heard, their work seen and written about."--Jaquette
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; art féministe; corps; cours; discours dominant; femmes* artistes; har4600; maternité; premier cycle; périodes historiques; représentation; sexisme; systèmes d'oppressions; thématiques

La procréation assistée, comment y voir clair? - Fédération du Québec pour le Planning des naissances (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; discipline; femmes*; maternité; médecine; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; sciences; thématiques

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques